2021
DOI: 10.1186/s12865-021-00420-0
|View full text |Cite
|
Sign up to set email alerts
|

TREM2 promotes natural killer cell development in CD3−CD122+NK1.1+ pNK cells

Abstract: Background Triggering receptor expressed on myeloid cells 2 (TREM2) signaling is considered to regulate anti-inflammatory responses in macrophages, dendritic cell maturation, osteoclast development, induction of obesity, and Alzheimer’s disease pathogenesis. However, little is known regarding the effect of TREM2 on natural killer (NK) cells. Results Here, we demonstrated for the first time that CD3−CD122+NK1.1+ precursor NK (pNK) cells expressed TR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…In order to systematically explore the potential immunological functions and the potential prognostic value of TREM2 across 33 cancer types, Cheng et al conducted a pancancer analysis based on datasets from The Cancer Genome Atlas, the Cancer Cell Line Encyclopedia, Genotype Tissue-Expression, cBioPortal and Human Protein Atlas, they used the ESTIMATE algorithm to calculate the immune scores across the 33 types of cancers, their results showed that the expression level of TREM2 was significantly positively correlated with immune scores in diffuse large B-cell lymphoma, acute myeloid leukemia and thymoma, and the levels of immune cell infiltration were significantly correlated with TREM2 expression in most types of malignancies (90), this indicated that TREM2 could function as a prognostic marker in various cancers because of its especial role in tumorigenesis and tumor immunity. Lately, Lee et al demonstrated for the first time that precursor natural killer (pNK) cells expressed TREM2, compared with wild type mice, the population of pNK cells and the expression levels of NK cell-activating receptors and NK cell-associated genes were all increased in TREM2-overexpressing transgenic mice, on the contrary, the inhibition of TREM2 signaling pathway by TREM2-immunoglobulin or PI3K inhibitor impacted the expression of NK cell receptor repertoire and downregulated the expression levels of NK cell-associated genes, thus significantly impaired the differentiation of NK cells, the results of this study collectively suggested again that TREM2 might act as a novel candidate for cancer immunotherapy (91).…”
Section: Application Of Trem2 In Cancer Immunotherapymentioning
confidence: 51%
“…In order to systematically explore the potential immunological functions and the potential prognostic value of TREM2 across 33 cancer types, Cheng et al conducted a pancancer analysis based on datasets from The Cancer Genome Atlas, the Cancer Cell Line Encyclopedia, Genotype Tissue-Expression, cBioPortal and Human Protein Atlas, they used the ESTIMATE algorithm to calculate the immune scores across the 33 types of cancers, their results showed that the expression level of TREM2 was significantly positively correlated with immune scores in diffuse large B-cell lymphoma, acute myeloid leukemia and thymoma, and the levels of immune cell infiltration were significantly correlated with TREM2 expression in most types of malignancies (90), this indicated that TREM2 could function as a prognostic marker in various cancers because of its especial role in tumorigenesis and tumor immunity. Lately, Lee et al demonstrated for the first time that precursor natural killer (pNK) cells expressed TREM2, compared with wild type mice, the population of pNK cells and the expression levels of NK cell-activating receptors and NK cell-associated genes were all increased in TREM2-overexpressing transgenic mice, on the contrary, the inhibition of TREM2 signaling pathway by TREM2-immunoglobulin or PI3K inhibitor impacted the expression of NK cell receptor repertoire and downregulated the expression levels of NK cell-associated genes, thus significantly impaired the differentiation of NK cells, the results of this study collectively suggested again that TREM2 might act as a novel candidate for cancer immunotherapy (91).…”
Section: Application Of Trem2 In Cancer Immunotherapymentioning
confidence: 51%
“…For example, targeting TREM2 in macrophages may acquire ideal efficacy since TREM2 can enhance immunosuppressive functions of these cells. However, in NK cells, targeting TREM2 may impede the maturation of NK cells and their ability to kill tumor cells [ 54 ]. More related studies are needed to confirm exactly how TREM2 works in tumors, and clinical trials are urgently needed to bring TREM2 to the clinic as soon as possible, thus contributing to new strategies for tumor immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with wild-type mice, hematopoietic stem cells from TREM2 overexpressed mice showed a higher tendency to differentiate into NK cells and showed increasing expression of NK cell-activated receptors and NK cell-related genes. The transfer of bone marrow cells from TREM2 overexpressed mice to tumor-bearing mice significantly restrains tumor progression [ 54 ]. These observations suggest that TREM2 enhances the differentiation and function of NK cells, and through this mechanism, TREM2 may fulfil an antitumor role.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the above studies, TREM2 has been shown to play an important role in the differentiation and effector function of NK cells. Overexpression of TREM2 promotes the differentiation of NK cells and enhances their killing activity against tumor cells by activating the PI3K/Akt signaling pathway ( 45 , 46 ). This difference in outcome may be due to the alteration of different signaling pathways by TREM2 and the exact mechanism remains to be further explored.…”
Section: Trem2 and Immunotherapymentioning
confidence: 99%